SARS-CoV-2 vaccine development: where are we now? - Kobinger, Gary (Henry Stewart Talks, 2020)
Vaccine development for SARS-COV-2: Current position, Different types of potential vaccines against COVID-19, New technologies and their implications, How past experience can support current research